A new species of Siphonoecetes Krøyer, 1845 Siphonoecetes (Centraloecetes) bulborostrum sp. nov. (Crustacea, Amphipoda, Ischyroceridae) from the western Mediterranean, coast of Iberian Peninsula - De-La-Ossa-Carretero, Jose Antonio; Martí, Amparo (Zootaxa, 2014)
An undescribed species of Siphonoecetes Krøyer, 1845 was found on Mediterranean coast of Iberian Peninsula. It was collected at the depth of 10 and 15 m near Alicante. Though it was previously found in Chafarinas Islands, this new species was not named and fully described. In the present paper, Siphonoecetes (Centraloecetes) bulborostrum sp. nov. is described. The species belongs to Centroloecetes subgenus, since it possesses bulbous ventroapical projection on peduncle of uropod 1 in males and a row of long pectinate setae on distal margin of peduncle of uropod 3. Siphonoecetes (Centraloecetes) bulborostrum sp. nov. (Crustacea, Amphipoda, Ischyroceridae) is easily distinguishable from the other Siphonoecetes reported in Iberian Mediterranean coast by presence of bulbous subrostral projection.